Rancang Bangun Purwarupa Plant Traffic Light Berdasarkan Kecepatan Pada Model Kendaraan Roda Empat Menggunakan Sistem Algoritma Logika Fuzzy - Regina Chelinia Erianda Putri; Ignasius Tegar Adiyanto; Oktavianus Ardhian Nugroho (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Generally, traffic light control systems in Indonesia only regulate based on fixed time. This becomes a problem when there is a buildup of vehicles on one side. From the results of field observations, one of the causes of this buildup is due to the setting of the lights that do not adjust the speed of the vehicle which is connected to the determination of the duration of the green light. In this study, a prototype system of plant traffic light control was created using a fuzzy logic system applied to the ATmega32 microcontroller. By comparing the speed of the car on each side, data was obtained from the algorithm that can be used to regulate the time of the traffic lights in each direction. The prototype that was created functions adaptively. From the results of this study using the prototype, it was found that by regulating the duration of the green light in the traffic light system, a success rate of 99.97% was obtained. Where if the vehicle speed is high, the green light duration value becomes fast and vice versa.